The Multifarious Endophytic Actinobacterial Isolate, Streptomyces tubercidicus UAE1, Combined With the Seaweed Biostimulant Further Promotes Growth of Avicennia marina - Alkaabi, Ameera K.; Ramadan, Gaber A.; Elddin, Afraa M. Taj; El-Tarabily, Khaled A.; AbuQamar, Synan F. (Frontiers in Marine Science, 2022)
Mangrove (Avicenna marina) is a "green lung" tree growing along the Arabian Gulf coastline in the United Arab Emirates. Here, we aimed to determine the impact of the application of a commercial seaweed extract (SWE) biostimulant and endophytic actinobacterial isolates on growth performance and endogenous hormonal levels of mangroves. Therefore, we isolated endophytic plant growth promoting (PGP) actinobacteria (PGPA) from mangrove roots; and evaluated their potential as biological inoculants on mangrove seedlings under greenhouse and open-field nursery conditions. Seven salt tolerant isolates had the ability to produce different levels of in vitro plant growth regulators (PGRs) and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase (ACCD), and to solubilize phosphorus. Accordingly, only one isolate, Streptomyces tubercidicus UAE1 (St), was selected based on its relative superiority in displaying multiple mode of actions and in successfully colonizing mangrove tissues for 15 weeks. In the greenhouse experiments, plants treated with either St or SWE significantly (P<0.05) improved dry biomass by 40.2 and 55.1% in roots and 42.2 and 55.4% in shoots, respectively compared to seawater-irrigated non-treated mangrove plants (control). However, St+SWE caused greater significant (P<0.05) increase in dry weight of roots (67.6%) and shoots (65.7%) than control plants. Following the combined treatment of St+SWE, in planta PGR levels were found to be greatly enhanced over the non-treated control or treated plants grown in sediments inoculated with St or supplied with SWE only. This was evident from the significant (P<0.05) increases in the photosynthetic pigments and production of PGRs, as well as the reduction in the endogenous ACC levels of plant tissues compared to those in other treatments. Tissue nutrient contents of seedlings also increased by at least two-fold in St+SWE treatment compared to control. Similar effects were observed on all growth parameters under natural open-field nursery conditions. By combining St with SWE, this does not only stimulate plant growth but also potentially has additive effects on mangrove ecosystem productivity in nutrient-impoverished soils in the Arabian coastal areas. This report is the first in the field of marine agriculture that uses SWE as a nutrient base for actinobacteria capable of producing PGRs and ACCD.